1990
DOI: 10.1002/kin.550220706
|View full text |Cite
|
Sign up to set email alerts
|

High temperature pyrolysis of methane in shock waves. Rates for dissociative recombination reactions of methyl radicals and for propyne formation reaction

Abstract: The pyrolysis of 2% CHI and 5% CHI diluted with Ar was studied using both a single-pulse and time-resolved spectroscopic methods over the temperature range 1400-2200 K and pressure range 2.3-3.7 atm. The rate constant expressions for dissociative recombination reactions of methyl radicals, CH, + CH3 + C2H, + H and CH, + CH3 + C2H4 + Ha, and for C,H4 formation reaction were investigated. The simulation results required considerably lower value than that reported for CH3 + CH, -+ C2H4 + H2. Propyne formation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Baulch 36,38,39 give nearly identical results with a bimolecular k(T) ∼ 6.5 × 10 -9 exp{-15430/T(K)} cm 3 s -1 . The latest work by Hidaka et al 40 gives a much lower value of 1.7 × 10 -10 exp{-16103/T(K)} cm 3 s -1 . Gordon et al 41 have calculated the transition state and obtain a barrier of 136 kJ/mol or ∆E/k ≈ 16 400 K. They conclude, "the concerted elimination of molecular hydrogen to form ethylene appears to be a very unlikely process".…”
Section: Experimental Design and Methods Of Data Reductionmentioning
confidence: 95%
“…Baulch 36,38,39 give nearly identical results with a bimolecular k(T) ∼ 6.5 × 10 -9 exp{-15430/T(K)} cm 3 s -1 . The latest work by Hidaka et al 40 gives a much lower value of 1.7 × 10 -10 exp{-16103/T(K)} cm 3 s -1 . Gordon et al 41 have calculated the transition state and obtain a barrier of 136 kJ/mol or ∆E/k ≈ 16 400 K. They conclude, "the concerted elimination of molecular hydrogen to form ethylene appears to be a very unlikely process".…”
Section: Experimental Design and Methods Of Data Reductionmentioning
confidence: 95%
“…As the heat transfer intensity between the cluster and environment increases, lifetime dependence (2), is transformed into Eq. (1). The key objective of this work is to study the character of the (2) to (1) transformation, as the heat transfer time τ th decreases to a finite value, and to determine the relation between the preexponential factorsξ and ξ of the decay of the thermalized and heatinsulated clusters.…”
mentioning
confidence: 99%
“…where k −is the Boltzmann constant, E a − is the decay activation (isomerization) energy, T − is the temperature of the environment in contact with the cluster, and the preexponential factor ξ has the dimension of time and is the inverse of the frequency factor of the corresponding process. In some approaches, this preexponential factor is considered constant (see, e.g., [1]), but in the general case it depends not only on the atomic cluster structure and the characteristic heat transfer time τ th between the cluster and environment, but also on the temperature, i.e., ξ = ξ(τ th , T ) (see, e.g., [2,3]).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bedarev et al based their work on the Kassel mechanism from the 1930s (4 reactions and 5 species) [42] and on another one (21 reactions, 13 species) developed by Hidaka et al [59]. The kinetic parameters were modified by Bedarev et al The comparison with the experimental data showed that the second mechanism was more suited to modelling the chemistry within the shock wave.…”
Section: Experiments and Kinetic Modellingmentioning
confidence: 98%